Severe thyrotoxicosis induced by tislelizumab: a case report and literature review - Huo, Liman; Wang, Chao; Ding, Haixia; Shi, Xuelian; Shan, Bin; Zhou, Ruoying; Liang, Ping; Hou, Juan (Frontiers in Oncology, 2023)
Immune checkpoint inhibitors (ICIs) have made significant breakthroughs in the treatment of a variety of malignancies. As its use increases, the unique immune-mediated toxicity profile of ICls are becoming apparent. We report a case of immune-related endocrine adverse events (irAE) in a patient with hepatocellular carcinoma treated with anti-programmed cell death protein 1 (PD-1) (tislelizumab). Although many irAEs have been reported, few cases of severe thyrotoxicosis have been described after immunotherapy in the literature. We present the case of a 49-year-old male who experienced a Grade 3 tislelizumab-related adverse reaction according to Common Terminology Criteria for Adverse Events (CTCAE5.0) and received methylprednisolone, thiamazole, and levothyroxine sodium tablets. Early identification of irAEs, risk factors, regular monitoring, use of steroids and/or immunoglobulins, and adjuvant supportive care are critical to the clinical prognosis of patients. It should be underlined that the tumor benefits of ICI therapy outweigh the risks associated with ICI-induced endocrine disorders, and ICI treatment should not be stopped or delayed except in rare cases (adrenal crisis, severe thyrotoxicosis). The familiarity of healthcare professionals with irAEs of the thyroid when thyrotoxicosis occurs is important to facilitate an effective diagnosis and appropriate treatment of this increasingly common thyroid disorder.